The analysis of supply chain of palm oil in PT. Tribakti Sarimas, Riau - Angga Pramana; Yelly Zamaya; Arum Rovarti Ningsih; Farida Hanum Hamzah; Yelmira Zalfiatri; Dihan Kurnia; Nita Rimayanti (AGROINTEK, 2022)
Supply chain at PT Tribakti Sarimas there are problems in the flow of materials. This research aims to identified supply chain and determine the priority of supply chain strategies at PT Tribakti Sarimas. This study has been conducted at PT Tribakti Sarimas Kuantan Singingi District Riau Province. The research methods used were qualitative descriptive. The respondents for this study are 30 farmers, 5 collectors, and 4 employees of PT Tribakti Sarimas. This research has shown that the supply chain of rubber at PT Tribakti Sarimas in Kuantan Singingi include farmers, collectors, PT Tribakti Sarimas amd consumers. The internal factor evaluation matrix has total score of 2.6919, while the external factor evaluation matrix has total score of 2.3707. The supply chain management strategy result at PT Tribakti Sarimas with AHP method shows that the chosen quantity weight is 0.279 and the chosen main alternative is the company maximizes the use of facilities and infrastructure to improve the quality of CPO with the weight is 0.165. Companies must pay attention to the quality of CPO by utilizing company facilities and infrastructure.